The Corona Case and the Increasing Cases of Racism and Xenophobia Against Ethnic Chinese in the World - Zatira, Zunsyika Zahra; Prakoso, Muhammad Pambudi (Universitas Muhammadiyah Yogyakarta, 2020)
The development of international relations studies is marked by the increasingly complex international issues that occur in the life of the world community. At present, the study of international relations is not only focused on the issue of war and peace but is developing on more substantial issues about human rights being manifested in daily life. Related to the realization of human rights, the world community is confronted with the problem of racism. A global phenomenon that has very strong historical roots and occurs in various fields of human life. Starting from politics, economics, socio-culture, to the field of sports. Unfortunately, acts of racial discrimination (racism) are increasingly developed by the existence of fanatical groups who like violent behavior, physical and non-physical. This research was conducted to find out how Racism and Xenophobia against ethnic Chinese developed very rapidly throughout the world with the outbreak of the Coronavirus that originated in China and throughout the world. The research method is a qualitative method with a literature study used secondary data. The results of this study indicate large increases in racism and xenophobic cases around the world during the Corona Virus. Understanding of this research may contribute to the awareness of people around the world about racism and xenophobia.